Public social spending in Africa: do the poor benefit? - Castro-Leal, Florencia, et al. (1999)
Education and health care are basic services essential in any effort to combat poverty and are often subsidized with public funds to help achieve that purpose. This paper examines the effectiveness of public social spending on education and healthcare in several African countries and finds that these programs favor not the poor, but those who are better-off. It concludes that this targeting problem cannot be solved simply by adjusting the subsidy program. The constraints that prevent the poor from taking advantage of these services must also be addressed if the public subsidies are to be effective. - Reproduced
Keywords: Health services - Africa; Education - Africa; Poor - Africa; Social services - Africa; Social services